2001
DOI: 10.1038/sj.bmt.1703081
|View full text |Cite
|
Sign up to set email alerts
|

Collection of hematopoietic stem cells from patients with autoimmune diseases

Abstract: Summary:We reviewed data from 24 transplant centers in Asia, Australia, Europe, and North America to determine the outcomes of stem cell collection including methods used, cell yields, effects on disease activity, and complications in patients with autoimmune diseases. Twenty-one unprimed bone marrow harvests and 174 peripheral blood stem cell mobilizations were performed on 187 patients. Disease indications were multiple sclerosis (76 patients), rheumatoid arthritis (37 patients), scleroderma (26 patients), s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
92
0
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(99 citation statements)
references
References 46 publications
0
92
0
4
Order By: Relevance
“…143 x 10 3 /µl), mas também foi escolhida para futuros estudos porque induziu uma resposta clínica mais prolongada do que nos pacientes condicionados com 100 mg/kg de CY (17- 19 vs. 2-3 meses) (64) . Em estudos retrospectivos, a mobilização com G-CSF isoladamente foi menos tóxica do que a combinada com ciclofosfamida (que causou mortalidade em 2,6% dos pacientes), mas induziu maior número de reativações da doença de base (65) e regimes de condicionamento mais agressivos causaram menos recaídas pós-transplante, mas maior mortalidade (11) . Assim, a tendência atual é utilizar mobilização com ciclofosfamida em dose baixa (2 g/m 2 combinada a G-CSF) e regimes de condicionamento de intensidade reduzida, subablativos, tanto nos transplantes autólogos como nos alogênicos, evitando-se o emprego de irradiação corporal total e esquemas poliquimioterápicos mieloablativos (66,67) .…”
Section: Possíveis Respostas Estratégias De Investigação Referênciaunclassified
“…143 x 10 3 /µl), mas também foi escolhida para futuros estudos porque induziu uma resposta clínica mais prolongada do que nos pacientes condicionados com 100 mg/kg de CY (17- 19 vs. 2-3 meses) (64) . Em estudos retrospectivos, a mobilização com G-CSF isoladamente foi menos tóxica do que a combinada com ciclofosfamida (que causou mortalidade em 2,6% dos pacientes), mas induziu maior número de reativações da doença de base (65) e regimes de condicionamento mais agressivos causaram menos recaídas pós-transplante, mas maior mortalidade (11) . Assim, a tendência atual é utilizar mobilização com ciclofosfamida em dose baixa (2 g/m 2 combinada a G-CSF) e regimes de condicionamento de intensidade reduzida, subablativos, tanto nos transplantes autólogos como nos alogênicos, evitando-se o emprego de irradiação corporal total e esquemas poliquimioterápicos mieloablativos (66,67) .…”
Section: Possíveis Respostas Estratégias De Investigação Referênciaunclassified
“…In particular, marginal or even failed mobilizations occurred in 9.2% of MS patients while inadequate BM progenitor cell harvests occurred in two patients. 12 Difficulties in stem cell mobilization procedure have also been described by Carreras et al 39 in 13.3% of cases in a series of 15 MS patients since one patient failed mobilization after two attempts while an additional patient reached the target CD34 þ cell yield following three leukaphereses.…”
Section: Cytokines In Ltbmc Supernatantsmentioning
confidence: 99%
“…[18][19][20][21][32][33][34] Studies in other autoimmune diseases have already shown abnormalities in BM hematopoiesis [7][8][9][10] capable of affecting the mobilization and/or the engraftment of stem cells in patients undergoing ASCT. [11][12][13] In the current study, we have evaluated the reserves and functional characteristics of BM hematopoietic progenitor cells and the hematopoiesis supporting capacity of BM stromal cells in MS patients and we have found that these patients displayed normal proportion of CD34 þ hematopoietic progenitor cells in the BMMC fraction and normal proportion of early CD34 þ /CD38 À and committed CD34 þ /CD38 þ cells. In contrast, the clonogenic potential of hematopoietic progenitor cells was found to be significantly reduced in these patients as was demonstrated by the low CFC number obtained from BMMCs and purified CD34 þ cells in short-term BM cultures and the low CFC recovery in NACs from LTBMCs.…”
Section: Cytokines In Ltbmc Supernatantsmentioning
confidence: 99%
See 2 more Smart Citations